2021
DOI: 10.1002/anie.202104682
|View full text |Cite
|
Sign up to set email alerts
|

Decatungstate‐Mediated C(sp3)–H Heteroarylation via Radical‐Polar Crossover in Batch and Flow

Abstract: Photocatalytic hydrogen atom transfer is a very powerful strategy for the regioselective C(sp 3 )-H functionalization of organic molecules. Herein, we report on the unprecedented combination of decatungstate hydrogen atom transfer photocatalysis with the oxidative radical-polar crossover concept to access the direct net-oxidative C(sp 3 )-H heteroarylation. The present methodology demonstrates a high functional group tolerance (40 examples) and is scalable when using continuous-flow reactor technology. The dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 44 publications
3
45
1
Order By: Relevance
“…This result was in line with the literature reporting non-bonding interactions (steric effects) [73] between a large group (i.e., phenyl) and an incoming decatungstate reactive intermediate (wO) in the C-H activation pathway [61]. Thus, the corresponding hydrogen atom abstraction (HAT) from the lone-selectivity where this steric interaction must be negligible provides a reasonable explanation for the observed side-selectivity with TBADT [74][75][76][77]. In contrast, the Mo 2 C-catalyzed twix-selectivity (100% yield of 6a') reflects a complete change in mechanism with that proposed via the HAT mechanism [78][79][80][81] (Scheme 5).…”
Section: Mechanstic Study On the Selective Oxygenation Of Alkenesupporting
confidence: 90%
“…This result was in line with the literature reporting non-bonding interactions (steric effects) [73] between a large group (i.e., phenyl) and an incoming decatungstate reactive intermediate (wO) in the C-H activation pathway [61]. Thus, the corresponding hydrogen atom abstraction (HAT) from the lone-selectivity where this steric interaction must be negligible provides a reasonable explanation for the observed side-selectivity with TBADT [74][75][76][77]. In contrast, the Mo 2 C-catalyzed twix-selectivity (100% yield of 6a') reflects a complete change in mechanism with that proposed via the HAT mechanism [78][79][80][81] (Scheme 5).…”
Section: Mechanstic Study On the Selective Oxygenation Of Alkenesupporting
confidence: 90%
“…It should be further noted that this two-step flow protocol enables access to pyrazoles bearing unactivated alkanes, which could not be prepared using our direct decatungstate-mediated C(sp 3 )–H azolation. 33 In addition, by adding 2-formylbenzoic acid derivatives ( D , E ) instead, the corresponding phthalazinones ( 34 – 37 , 55–69%) could be obtained by means of this streamlined flow process ( Scheme 3 A). Finally, we also demonstrated that the protected hydrazines can be readily converted to the corresponding primary amines via hydrogenation ( 38 , 87%) ( Scheme 3 B).…”
Section: Resultsmentioning
confidence: 99%
“…and others, either by a NIS‐mediated addition of nitrogen‐based nucleophiles [19] or an epoxidation of the double bond followed by a ring opening [20] . N ‐glycosylation of glycals was recently achieved by photoredox catalysis [21] . However, to the best of our knowledge, N ‐glycosylation of C2‐alkylated glycals is unknown.…”
Section: Methodsmentioning
confidence: 99%